Construction of a facile separation and recycle photocatalyst: g-C3N4/diatomite-based porous ceramic composite. Issue 8 (15th April 2023) - Wang, Mengfan; Cui, Zhentao; Xu, Hongliang; Li, Mingliang; Song, Bo; Wang, Hailiang; Shao, Gang; Wang, Hailong; Lu, Hongxia; Zhang, Rui
Abstract: Melamine pretreated with hydrochloric acid was mixed with diatomite-based porous ceramics ( Ф 18 × 6 mm in size) and then heated from room temperature through an intermediate holding temperature up to 550 °C and calcined for 2 h to obtain g-C3 N4 /diatomite-based porous ceramic composites (xHCN/D, x = 310, 355, 400, representing the holding temperature in the intermediate stage). The samples were characterized by XRD, FT-IR, SEM, UV–Vis, PL, etc.. Rhodamine B (RhB) solution was used as the target pollutant to evaluate the photocatalytic activity of the samples. The results show that the phase composition of xHCN/D composites included g-C3 N4 and those in diatomite-based porous ceramic. The photocatalytic activity of xHCN/D composites were better than that of 355CN/D composite synthesized under the same condition as 355HCN/D but using pristine melamine, although the loading rates of g-C3 N4 on xHCN/D were much smaller than that on 355CN/D. The photocatalytic activity of xHCN/D changed with the variation of x, and 355HCN/D exhibited the optimum photocatalytic performance as well as excellent cycling stability and recoverability. 355HCN/D (1 g) degraded 86.74% of RhB molecules (2 mg/L, 100 mL) in 200 min, whose reaction rate constant was 1.45 times that of 355CN/D. In addition, the photocatalytic activity of 355HCN/D particles (3–4 mm in size) was superior to that of 355HCN/D disc. The enhanced UV–visible light absorption ability, narrowed band gap and the decreased photo-generated electron-hole recombination rate of 355HCN/D were ascribed to the significantly reduced size and appropriate amount of g-C3 N4 sheets loaded uniformly on the surface of diatomite-based porous ceramic, due to the synergistic action of acid-treating to melamine and holding at an intermediate temperature. This work provides a strategy for preparing high performance photocatalysts with a facile separation and recycle ability.